Angiofibromatous appendix of the lip mucosa. - Rana, P.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2006)
No similar cases were found in the relevant literature. No similar cases were found in the relevant literature. An appendix can be found level with the lines of embryo fusion or in sites of embryo residua (3), such as the first branchial arch (preauricular appendices and accessory tragi of the neck). However, it is not the case of our patient. Multiple angiofibromas, namely benign simultaneous proliferations of fibroblasts and vessels are found in syndromes predisposing to neoplasia, such as multiple endocrine neoplasia type I (1) and tuberous sclerosis. An angiofibromatous structure can be also found in some benign gingival neoformations, in fibrous papule of the nose and in the pearly papules of the crown of the glans and of vagina orifice ("irsuties papillarum penis et vulvae"). Angiofibromatous papillae, sometimes elongated, can be found more often in the vulvar region, also in tuberous sclerosis (2).